Evaluation of Homeschooling Programs Using the Metfessel-Michael Model Improving the Quality of Student Learning - Amelia Dewanti; Evita Yuliatul Wahidah (Jurnal Cahaya Edukasi, 2026)
Homeschooling education in Indonesia faces challenges such as dependence on parental quality, lack of regulation, and variation in learning outcomes, thus requiring systematic evaluation to improve the quality of student learning. The Metfessel-Michael model offers a comprehensive approach by evaluating context, input, process, and product, thereby supporting curriculum personalization and ongoing feedback. This research aims to integrate these models to overcome the gap between the ideals and realities of homeschooling. The study employed a Systematic Literature Review (SLR) adhering to PRISMA guidelines from 2020 to 2025. A total of 17 articles were selected after identification, screening, feasibility, and inclusion screening, followed by a qualitative analysis based on PRISMA diagrams. The application of the Metfessel-Michael Model enhances academic achievement, student engagement, and social-emotional development through a SWOT analysis, with strengths in flexible curriculum design and opportunities for Montessori integration and blended learning. The weaknesses include variations in outcomes due to parental limitations, while the threat of weak regulation can be addressed with continuous evaluation.